Pseudo-impulse tail current shaping for phase noise reduction in CMOS LC oscillators. (April 2018) - Jafari, Bahram; Sheikhaei, Samad
Abstract: In this paper, a low phase noise oscillator using tail current shaping method is presented. The current shaping is achieved using two paths for current disconnection and current injection, as a result of which, the total tail current is shaped to a sharp and sawtooth waveform, close to an impulse. Each switching transistor is ON only in 22% of an oscillation period, and tail current is mostly supplied to these transistors near the outputs peak points. In those moments, the oscillator sensitivity to noise sources is minimum. The proposed oscillator is designed and simulated in 0.18 μm RF CMOS technology with 1.8 V supply, and using the inductor model offered by the process, with quality factor of 11. Post layout simulations predict an oscillation frequency of 1.65 GHz, and phase noise of −127.7 dBc/Hz at 1 MHz offset, which is 6.3 dB better than that of simple cross coupled oscillator with the same core oscillator power consumption of 2.2 mW. The proposed circuit, however, consumes an extra power of about 1.9 mW for the added current shaping circuits. Compared to conventional tail current shaping technique, the proposed oscillator offers better tail current shaping, and a much higher start-up current and gain, which is desirable. Graphical abstract: